THE IMPACT OF INFLATION ON FINANCIAL STATEMENT DATA - Ass. Lec. Ammar Mohamed Hussein; Ass. Lec. Ahmed Obaid Mahmoud Mohsin; Ass. Lec. Mohanad Abed Hussein (Scholar Express Journals, 2024)
The Iraqi currency has suffered due to high inflation, which has been ravaging the country for more than 40 years, leading to a weakening in value over time. and due to most companies in Iraq depend on historical cost, this research came to find out the impact of inflation on data of accounting and the information that provide through financial statements in Iraq environment A questionnaire form was distributed to a sample size of 148 accountants and board members. Where it turns out that the direction of the sample was in agreement with the hypothesis related to the impact of inflation on the quality of financial statements, and must use the alternative methods to avoid historical cost problems.
Keywords: Inflation; Financial Statements; Historical cost